Surgical inaccuracy or tumour-related pelvic resections and implications on the oncologic outcomes - Sharifudin, Mohd Ariff; Wan Ismail, Wan Faisham Numan; Wan, Zulmi; Mat Zin, Nor Azman; Mohamed Amin, Mohamed Azril; Goh, Kian Liang (2014)
Introduction: The rates of cure for pelvic tumours are still lower compared to tumours involving the long bones even with advancement in treatment modalities. Safe surgical margins, an important prognostic factor for oncologic outcomes, are difficult to achieve when performing surgical resections for bone and soft tissue tumours involving the pelvis. We evaluated the accuracy of surgical margins achieved in pelvic tumour resections, its associated factors, as well as the oncologic outcomes. Materials and Methods: 64 cases of pelvic tumours of various types, whom underwent internal (limb-salvage) or external hemipelvectomy in a single tumour referral center were included. Various clinicopathologic factors were analyzed in relation to achieving a negative microscopic margin in tumour resections. Analysis included survival time to local recurrence, distant metastasis, and disease-specific death of patients, as well as factors associated with the oncologic outcomes. Results: Mean age at time of surgery was 39.8 years (range 8 to 79 years). Majority of cases were primary tumours (76.56%), mostly were chondrosarcoma (n=14) and osteosarcoma (n=13). 23 patients underwent external hemipelvectomy and 41 patients subjected for internal hemipelvectomy of various types of resections. Majority (71.88%) of cases were treated with curative intention. 14 of 37 cases (37.84%) attempted for wide resection had positive microscopic margins. Incidence of positive microscopic margin was higher in cases with wide contaminated margins (56.25%). Factors associated with positive microscopic margin include tumour occurrence, tumour volume, tumour stage, types of surgery (amputation or limb-salvage) and types of pelvic resections. Local and distant recurrence rate were higher when margins were positive. Paradoxically the disease-specific death rate was lower in cases with positive margins. Conclusion: The probability of achieving a clear microscopic margin in attempted wide resections was as low as 50% only, similar to a previous published experimental study. Internal hemipelvectomy provides significantly better disease-specific survival rate, hence justified with proper indication and selection of patients. Microscopic margin was a prognostic factor for all three primary endpoints of this study, but was not statistically proven as an independent prognostic factor.